Perspektywa oceniania a spostrzegana atrakcyjność twarzy upiększanych cyfrowo: różnice międzypłciowe = The perspective of judgements and the perception of facial attractiveness modification: gender differences - Gawron, Dagmara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the differences in the perception of facial attractiveness modification depending on the perspective of judgements and gender. In the experiment (N = 168), participants chose which of the 9 beautified photos was the most attractive. Then an observer repeated this same procedure for this participant. In this study, there were two conditions.
Keywords: atrakcyjność twarzy; preferencje estetyczne; modyfikacja wyglądu; różnice międzypłciowe; faces; attractiveness judgment; body modification; gender